2008
DOI: 10.1111/j.1939-1676.2008.0163.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Cats with Naturally Occurring Chronic Kidney Disease (2000–2002)

Abstract: Background: Duration of survival of cats with naturally occurring chronic kidney disease (CKD) is poorly characterized. Hypothesis: Stage of kidney disease based on serum creatinine concentration (SCr) at the time of diagnosis and after correction of prerenal azotemia is strongly associated with duration of survival in cats.Animals: Two hundred and eleven client-owned cats with naturally occurring CKD evaluated between April 2000 and January 2002.Methods: Retrospective case review of 733 cats with SCr 4 2.3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
162
2
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(184 citation statements)
references
References 15 publications
11
162
2
9
Order By: Relevance
“…Plasma creatinine concentration, UPC, and PCV were independent predictors of all‐cause mortality in the present study. Plasma creatinine concentration was found to be associated with survival time in this, and in previous studies of cats with CKD,17, 31, 36 and median survival times for each IRIS stage in this study are similar to those reported previously 16, 37. UPC has previously been shown to be an independent predictor of survival time in cats with CKD,31 and in this study being classified as borderline proteinuric (UPC 0.2–0.4) or proteinuric (UPC > 0.4) under the IRIS proteinuria classification scheme6 was associated with a greater than 2‐times increase in risk of death.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Plasma creatinine concentration, UPC, and PCV were independent predictors of all‐cause mortality in the present study. Plasma creatinine concentration was found to be associated with survival time in this, and in previous studies of cats with CKD,17, 31, 36 and median survival times for each IRIS stage in this study are similar to those reported previously 16, 37. UPC has previously been shown to be an independent predictor of survival time in cats with CKD,31 and in this study being classified as borderline proteinuric (UPC 0.2–0.4) or proteinuric (UPC > 0.4) under the IRIS proteinuria classification scheme6 was associated with a greater than 2‐times increase in risk of death.…”
Section: Discussionsupporting
confidence: 91%
“…Median survival time for cats in this study was 367 [147, 813] days, which is similar to other reports in the literature 16, 31, 35. Plasma creatinine concentration, UPC, and PCV were independent predictors of all‐cause mortality in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Persian, Abyssinian, Siamese, Ragdoll, Maine coon but the current evidence base for these breed predispositions is low. 5,24,25 Similarly although the study above suggested a predisposition in neutered male cats, overall other studies have not supported a sex predisposition.…”
Section: Association Of Chronic Kidney Disease With Demographic Envimentioning
confidence: 56%
“…2 Diagnosis of renal dysfunction in the early stage is essential for preventing or delaying additional renal damage. 3,4 A direct measurement of glomerular filtration rate (GFR) is considered the gold standard for evaluating kidney function. 5 However the measurement is expensive and time-consuming.…”
Section: Introductionmentioning
confidence: 99%